The impact of percutaneous coronary intervention of chronic total occlusions on left ventricular function and clinical outcomes - Christakopoulos, Georgios E.; Tarar, Muhammad Nauman J.; Brilakis, Emmanouil S. (Journal of Thoracic Disease; Vol 7, No 7 (July 30, 2015): Journal of Thoracic Disease, 2015)
A meta-analysis by Hoebers et al. reported that successful chronic total occlusion (CTO) recanalization resulted in an increase in left ventricular (LV) ejection fraction by 4.44% (P